Association of Islamic Banking and Financial Institution Malaysia / Muhammad Haqeem Zulkiply - Zulkiply, Muhammad Haqeem (Faculty of Business and Management, 2023)
My internship at the Association of Islamic Banking and Financial Institution Malaysia lasted for a total of twenty-four weeks, and I've documented my experiences in this Industrial Training Report. My goal in writing this report was to detail my experience over my 24-week period of industrial training. In it, I detail my time spent in industrial training over the course of the past few years, touching on topics like the people I met, the contacts I made, my efforts to adjust to the workplace, my time spent in the field, and the professional and personal growth I experienced as a result. My background, the company's background, my training experience, a SWOT Analysis, a TOWS Analysis, suggestions, and a conclusion are all included in this industrial training report. SWOT analysis. This report will evaluate my work thus far and make suggestions on how I might improve moving forward. The word 'International' is often understood to refer to any form of diplomatic, cultural, commercial, or security cooperation between nations on a worldwide scale. I am now completing my Industrial Training at the Association of Islamic Banking and Financial Institutions of Malaysia (AIBIM); thus, the course 'International Business' is very applicable to my studies. During my time as an intern at AIBIM, I have had several opportunities to network with my foreign peers at AIBIM-sponsored events and programs. Therefore, this research will delve deeper into this significance by doing a thorough SWOT and TOWS Analysis of its external interactions.